2014
DOI: 10.1111/jce.12467
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Asymptomatic Longstanding Persistent Atrial Fibrillation: Impact on Quality of Life, Exercise Performance, Arrhythmia Perception, and Arrhythmia‐Free Survival

Abstract: Successful ablation improves exercise performance and QoL in asymptomatic LSP-AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…The pathophysiology underlying HF and AF resulting in compromised stroke volume is the likely basis of altered exercise tolerance. [15][16][17][18]30 Thus, the significant improvement in 6MWD could reflect betterment in cardiac contractility and rhythm resulting in restoration of a more efficient cardiac contraction following successful ablation. Our results further corroborated the correlation between ablation success and improvement in QoL.…”
Section: -29mentioning
confidence: 99%
“…The pathophysiology underlying HF and AF resulting in compromised stroke volume is the likely basis of altered exercise tolerance. [15][16][17][18]30 Thus, the significant improvement in 6MWD could reflect betterment in cardiac contractility and rhythm resulting in restoration of a more efficient cardiac contraction following successful ablation. Our results further corroborated the correlation between ablation success and improvement in QoL.…”
Section: -29mentioning
confidence: 99%
“…Mohanty et al 6 found that successful ablation improved the exercise performance and quality of life in 61 asymptomatic patients with longstanding persistent AF. However, 25 patients experienced AF recurrence and 21 (84%) were symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Up until now, data on catheter ablation for patients with asymptomatic AF are limited. 5,6 Whether patients with asymptomatic AF could benefit from ablation remains unclear. In the present study, we investigated the Lingmin Wu and Yanlai Lu contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in the impact of AF on the health-related quality of life (HRQoL), which has been considered as an important patient-centered health outcome measurement (Mohanty et al 2014). However, the results of previous studies have been conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…There were also studies with results suggesting that the HRQoL in AF patients might initially decrease, but improve progressively in the next few months or years (Jenkins et al 2005;Reynolds et al 2006). Mohanty et al (2014) has also found that even in patients with asymptomatic longstanding persistent AF, successful ablation could still improve HRQoL. Several types of weakness in methodology have been proposed as contributors to such conflicting results (Thrall et al 2006;Aliot et al 2014).…”
Section: Introductionmentioning
confidence: 99%